Analysis of Interest Rate Swaps and Selected Quantitative Methods - Slabý, Pavel; Málek, Jiří, 1953-; Fučík, Vojtěch; Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví (2018)
The goal of this thesis is to present the concept of interest rate swaps and selected quantitative methods related to pricing of these derivatives and their risk management. The thesis starts with description of the plain vanilla interest rate swap and its most common variations. The author continues with explanation of selected quantitative methods, these include bootstrapping, linear interpolation, convexity adjustment, calculation of forward rates and constructing the zero-coupon curve. Duration, scenario analysis, DV01/PV01 indicator and several other risk management methods related to interest rate swaps are described as well. Principal component analysis is emphasized as one of the tools that is used to describe the development of interest rates. The analysis is applied on an example of EUR swap rates. The described methods are at the end of the thesis utilized to price a real-life interest rate swap.
Vedoucí práce: Jiří Málek
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví, 2018
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2018
Způsob přístupu: Internet
Keywords: finanční inženýrství [obor dipl. práce]; diplomové práce; master's theses